A STUDY ON THE PRAWN FISHERY OF NETRAVATI-GURUPUR ESTUARY, MANGALORE - Sukumaran, K K; Thippeswamy, O; Muniyappa, Y (Indian Journal of Fisheries, 2011)
Eight species of penaeids, one species of sergestid and three species of caridian were noticed in the Netravati-Gurupur estuary. The penaeids Penaeus indicus, P. monodon, Metapenaeus dobsoni, M. moyebi and M. monoceros were common. Peak recruitments of earty juveniles of P. indicus were in May, June and December and of M. dobsoni were in January and June-September